IFPA Award in Placentology Lecture: Preeclampsia, the decidual battleground and future maternal cardiovascular disease - Staff, A; Redman, C (2014)
The decidua basalis is one of the frontiers between placenta and mother. Its spiral arteries ensure that the placenta and fetus have adequate access to the maternal circulation, without compromising maternal health. Normally this requires a tightly regulated collaboration between tissues of genetically different individuals. But like all frontiers it can become a battlefield. The decidua is difficult to sample systematically. Some of the problems have been resolved by our vacuum suction method. We review the technique and how it has contributed to what we know of decidual tissue, especially when it becomes a battlefield in preeclampsia, with its increased oxidative stress and inflammation. Acute atherosis is a poorly studied decidual lesion of late pregnancy, which mainly affects the decidual tips of spiral arteries in preeclampsia. It is characterized by lipid-filled foam cells and resembles early atherosclerosis. Poorly remodelled spiral arteries seem to be especially susceptible. The underlying mechanisms are largely unknown, but are likely to be similar to those of atherosclerosis and primarily the consequence of vascular inflammation. Acute atherosis also occurs in other pregnancy complications, even in normal pregnancies. It appears not to be confined to maladapted spiral arteries nor be caused by hypertension. It is important that foam cells result from inflammatory stimulation of macrophages. Hence, we propose that decidual inflammation of multiple causes underlies acute atherosis, with or without preeclampsia. Women suffering from preeclampsia have an augmented risk of cardiovascular disease later in life and of premature death. Acute atherosis may more specifically identify those women at augmented risk for such later cardiovascular disorders, whether or not it is associated with preeclampsia. © 2013 Published by IFPA and Elsevier Ltd.